Ethno-ornithology of Temuan Community In Ledang, Johor - Norazlimi, Nor Atiqah; Mohd Sarif, Amirah (Journal of Sustainable Natural Resources, 2021)
Ethno-ornithology is the study of the relationship between people and birds. It is a natural scientific approach that explains the relationship between people’s knowledge and the use of birds in their culture. Temuan community is one of the aborigine ethnics in Malaysia. They practice lifestyles that closely associated with nature. Therefore, this study aimed to investigate the ethno-ornithology knowledge and practice by Temuan Community lived around the Gunung Ledang National Park, Johor, Malaysia. A set of questionnaires was distributed to 40 respondents from the Temuan community to gather the information of birds used in their daily activities. In addition, the information was also obtained from the interview session with the head of the village (Tok batin). The identification of the birds obtained from the questionnaire and interview was further confirmed by using reliable resources. A total of 29 bird species was successfully identified. Temuan community used birds in their daily life in many ways such as, food, pet, folklore, entertainment, and many more. Understanding ethno-ornithology between local community and avifauna is good as it helps conservationists to keep track of bird species they use and identify the sustainable ways of this practice that align with the conservation of avifauna species.